2012
DOI: 10.1088/1674-1056/21/9/090402
|View full text |Cite
|
Sign up to set email alerts
|

Non-equilibrium Landauer transport model for Hawking radiation from a Reissner—Nordstrom black hole

Abstract: The recent work of Nation et al in which Hawking radiation energy and entropy flow from a black hole can be regarded as a one-dimensional (1D) Landauer transport process is extended to the case of a Reissner-Nordstrom (RN) black hole. It is found that the flow of charge current can also be transported via a 1D quantum channel except the current of Hawking radiation. The maximum entropy current, which is shown to be particle statistics independence, is also obtained.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In Refs. [19,20], the method has been extended to some more complicated black holes with nonzero chemical potential and it is found that charge flux and gauge flux can also be viewed as a 1D Landauer transport process.…”
Section: Introductionmentioning
confidence: 99%
“…In Refs. [19,20], the method has been extended to some more complicated black holes with nonzero chemical potential and it is found that charge flux and gauge flux can also be viewed as a 1D Landauer transport process.…”
Section: Introductionmentioning
confidence: 99%